2022
DOI: 10.1186/s13023-022-02573-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient centered guidelines for the laboratory diagnosis of Gaucher disease type 1

Abstract: Gaucher disease (GD) is an autosomal recessive lysosomal storage disorder due to the deficient activity of the acid beta-glucosidase (GCase) enzyme, resulting in the progressive lysosomal accumulation of glucosylceramide (GlcCer) and its deacylated derivate, glucosylsphingosine (GlcSph). GCase is encoded by the GBA1 gene, located on chromosome 1q21 16 kb upstream from a highly homologous pseudogene. To date, more than 400 GBA1 pathogenic variants have been reported, many of them derived from recombination even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 183 publications
(241 reference statements)
0
12
0
Order By: Relevance
“…CCL18 is a member of the C-C chemokine family, and like chitotriosidase, it accumulates in the alternatively activated macrophages present in Gaucher cells in GD. An increase in CCL18 can also be found in various lysosomal and non-lysosomal diseases, similar to chitotriosidase [7].…”
Section: Discussionmentioning
confidence: 93%
“…CCL18 is a member of the C-C chemokine family, and like chitotriosidase, it accumulates in the alternatively activated macrophages present in Gaucher cells in GD. An increase in CCL18 can also be found in various lysosomal and non-lysosomal diseases, similar to chitotriosidase [7].…”
Section: Discussionmentioning
confidence: 93%
“…However, it was always noted that there is a range in enzyme activity, dependent on the laboratory and source of protein tested. The incorporation of measurement of glucosylsphingosine (lysoGL1, lysoGb1) levels can now aid in confirming the enzymatic analysis, as this lipid substrate is elevated in samples from patients with GD (Dardis et al, 2022; Revel‐Vilk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If patients were genotyped previously with screens for a limited number of mutations, it may be advisable to repeat the genotyping with an analysis of the entire GBA1 gene, especially when there is a question regarding the diagnosis. Today, especially in the newborn period, assays for glucocerebrosidase activity are increasingly performed on dried blood spots, which are often stored and transported by mail, and may have compromised accuracy, requiring validation by careful GBA1 sequencing and glucosylsphingosine assays (Dardis et al, 2022) Furthermore, even patients with two identified mutations can potentially have both on the same allele (Balwani et al, 2011), so collecting samples from family members can be useful. Since variant T369M and E326K (p.E365K), a second non‐GD‐causing variant (Park et al, 2002), are frequently encountered in the general population, counselors will need to be informed regarding the implications of these alleles, which may mildly reduce glucocerebrosidase activity but do not cause GD, especially as they may be identified in newborn screening.…”
Section: Discussionmentioning
confidence: 99%
“…Results can be influenced by anemia, leucopenia, and recent transfusions [ 15 ]. Pre-analytical conditions for sampling and storage conditions are also important since enzyme activities in DBS are highly sensitive to heat and humidity [ 50 , 51 ]. Regarding acid sphingomyelinase activity, contrary to most other lysosomal enzymes, the assay had so far been restricted to a very limited number of laboratories, due to its technical complexity.…”
Section: Diagnostic Investigationsmentioning
confidence: 99%
“…Results can be influenced by anemia, leucopenia, and recent transfusions [15]. Pre-analytical conditions for sampling and storage conditions are also important since enzyme activities in DBS are highly sensitive to heat and humidity [50,51].…”
Section: Biological Sources For Assay Of Acid Sphingomyelinase Activitymentioning
confidence: 99%